MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA DUKUH, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Jamaludin (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Micro, small and medium enterprises or rural MSMEs have a relatively large contribution to the macro economy in both regional and national contexts. However, in practice, there are many obstacles and obstacles faced by MSMEs, one of which is experiencing difficulties in capital capacity. The majority of capital owned by rural MSMEs is not through formal financial institutions, but rather their own capital. Therefore, through community service by programming sharia financing, it aims to help restore the economic conditions of rural MSMEs. With a solutive and applicable sharia financing model, it is hoped that there will be an increase in financial inclusion for rural MSMEs. This is aimed at serving the community in Dukuh Village, Cibungbulang District, Bogor Regency.